Investigation on the technical and economic benefits of implementing biomass gasifier in clay brick manufacturing industries. (October 2022) - Murugan, P.C.; Saji Raveendran, P.; Joseph Sekhar, S.; Navaneethakrishnan, P.; Beno Wincy, W.; Glivin, Godwin
Highlights: Clay brick industries can use biomass gasifier to enhance energy efficiency. Producer gas brick exhibits physical properties on par with the ASTM standards. Gasifier fired kilns can save 30% of biomass consumption. Economic benefits in the implementation of biomass gasifier in brick industries. Abstract: The direct burning of solid fuel in brick industries leads to high fuel cost, low energy conversion efficiency and a huge amount of CO2 emissions. The impact of the above issues can be reduced with the implementation of biomass gasifiers in the brick-firing kilns. However, the flame temperature of producer gas must be greater than 875 °C to maintain the required temperature of the kiln and ensure vitrification of bricks. Moreover, economic viability is a must to implement the above concepts. In this study, different types of biomasses available in a region were studied to select the four potential feedstocks, and a 115 kW (thermal) gasifier was used to produce bricks from a small kiln of 1000 bricks capacity. The compressive strength, water absorption capacity and ultrasonic pulse velocity were found as 8.0–9.25 N/mm2, 11–12 % and 1200–1600 m/s respectively, which ensured the durability of the bricks as per ASTM standards. For the tested conditions, specific energy consumption of brick was 2–3 MJ/kg. According to this study, the brick manufactured through the suggested method could achieve properties as per ASTM standards. The proposed system's lower operating costs resulted in a payback period varying from 4 to 8 years.